A Pan-Cancer Analysis of the Oncogenic Role of WD Repeat Domain 74 in Multiple Tumors - Wu, Xiaoxuan; Song, Peng; Wang, Shun; Qian, Zhirong; Ying, Jianming; Gao, Shugeng; Li, Wenbin (Frontiers in Genetics, 2022)
Although emerging patient-derived samples and cellular-based evidence support the relationship between WDR74 (WD Repeat Domain 74) and carcinogenesis in multiple cancers, no systematic pan-cancer analysis is available. Our preliminary research demonstrated that WDR74 is over-expressed in lung squamous cell carcinoma (LUSC) and related with worse survival. We thus investigated the potential oncogenic roles of WDR74 across 33 tumors based on the database of TCGA (The Cancer Genome Atlas) and GEO (Gene Expression Omnibus). WDR74 is highly expressed in most cancers and correlated with poor prognosis in several cancers (all p < 0.05). Mutation analysis demonstrated that WDR74 is frequently mutated in promoter regions of lung cancer. Moreover, we found that CD8+ T-cells and the fibroblast infiltration level increased in WDR74 over-expressed cancer cells. The GO (Gene Ontology) enrichment analysis of the WDR74 pathway revealed its participation in cellular biogenesis of the RNA metabolism and its critical role in cancer initiation and progression through the tumor cell energy metabolism. Our first pan-cancer study inferred a relatively comprehensive understanding of the oncogenic roles of WDR74 across various cancers.